MEMPREDIKSIKAN TURNOVER PADA KARYAWAN PERUSAHAAN GARMEN: Pengaruh Praktek Pengembangan Sumber Daya Manusia dan Kepercayaan Terhadap Organisasi - PURI PALUPI, DYAH AYU (STIE Totalwin Semarang, 2011)
This study examined variables that predict employee turnover intentions. Influence of trust in the organization as a mediator variable in this relationship was also examined. Questionnaires completed by 380 employees of the companys operating divisions garment. Hierarchical regression analysis used to test this relationship. The results was supported the hypothesis, the result states that in order to enhance the trust of employees in the organization and to reduce turnover intentions, garment companies needs to maintain the continuity and development of training programs, conduct a formalÂ and fair appraisal system , provide a clear and adequate career progression for employees. Suggestions and limitations for future research are also given.